Konsep Fairness John Rawls, Kritik dan Relevansinya - Sunaryo Sunaryo (The Constitutional Court of the Republic of Indonesia, 2022)
Justice is very fundamental in a pluralistic society. Rawls's view of justice, which is understood as fairness, tries to offer how we organize a pluralistic society fairly. This view is crucial to be considered. The concept of fairness is understood as the ability to act that is acceptable and supported reciprocally. In Rawls's view, the existence of mutual acceptance and support from free and equal citizens without intimidation and pressure signifies that the agreement is fair. He called this kind of attitude reasonableness. In a just society, people must be able to act reasonably. With this capacity, they will agree on the principles of justice, which will be the basis of their social unity. The concept of fairness is essential for a pluralistic society like Indonesia. If we fail to bring justice in a pluralistic society, then our unity as a society will be under serious threat.